Development of Control Structure for Hybrid Wind Generators with Active Power Capability. (2nd September 2014) - Niroomand, Mehdi; Won, Dong-Jun
Abstract : A hierarchical control structure is proposed for hybrid energy systems (HES) which consist of wind energy system (WES) and energy storage system (ESS). The proposed multilevel control structure consists of four blocks: reference generation and mode select, power balancing, control algorithms, and switching control blocks. A high performance power management strategy is used for the system. Also, the proposed system is analyzed as an active power filter (APF) with ability to control the voltage, to compensate the harmonics, and to deliver active power. The HES is designed with parallel DC coupled structure. Simulation results are shown for verification of the theoretical analysis.